The innovative biodiversity monitoring framework called TerraBio has resulted in private sector buy-in supporting performance assessment in sustainable business models. - Francesconi, Wendy; Molina, Luis; Perez, Jorge Andres; Tello, Jhon Jairo; Caldas De Oliveira, Bernardo (2024)
TerraBio, an innovative approach for monitoring biodiversity and environmental impact, is being used by private sector enterprises in the Brazilian Amazon to generate evidence on the effects of business models on naturally occurring species and vegetation. This has resulted in various context-dependent actions targeting biodiversity conservation, and increased awareness on science - based performance and impact approaches, which are leveraged by these enterprises to access green markets through greater transparency and environmental compliance.